S4index: Does it only measure ionospheric scintillation? - de Oliveira Nascimento Brassarote, Gabriela [UNESP] (2018)
The study of ionospheric scintillation has played a critical role in ionospheric research and also in satellite positioning. This is due to the growing influence of GNSS in navigation and remote sensing activities and also because the scintillation severely degrades the performance of this system. The main parameter that has been used to investigate the ionospheric scintillation impact on quality of GNSS satellite signals is the S4 index. However, we show that other effects such as multipath may mask the scintillation effects. Furthermore, we propose a method to separate the effect of multipath from scintillation in the S4 index by a non-decimated wavelet multiscale decomposition, which is shift invariant and more appropriate to use in the analysis of time series. The results show that the multipath effect is evident in the smoother scales of multiscale decomposition by wavelet in the weak scintillation period. Once identified and estimated, this effect can be removed from the S4 index series during strong scintillation periods and it becomes not significant in the scintillation S4 index wavelet analysis. Investigations using data from different stations and satellites demonstrate that the effect of ionospheric scintillation varies with station location and elevation angle of the satellite. Therefore, each case must be treated individually.